Antimalarials: A Patents Landscape Study (2015-Present): Life Sciences-Antimalarials - Yadav, Narender; Kumar Kumawat, Mukesh; Ajmal, Gufran; Kumar Sharma, Manoj (International Journal of Life Science and Pharma Research, 2022)
Abstract: Plasmodium falciparum, Plasmodium vivax, Plasmodium ovale, Plasmodium malariae, and P. knowlesi are five Plasmodium species that cause malaria, a life-threatening parasitic disease. In the developing world, the rapid development of Plasmodium falciparum resistance to currently available treatments has become a serious health concern. This work reports a patent landscape analysis of patent documents related to antimalarial. The patent search was conducted using the commercially available CAS SciFinder database and the open-source patent database, The Lens. Seven hundred ninety-seven patents from The Lens and 1172 patent Sci-finder were exported using the antimalarial drug as a keyword. After the initial screening, 58 patent documents were shortlisted for in-depth analysis. After analysis, it was found that most of the top applicants come from the United States and Switzerland, which shows that market protection is more important in these two countries. The top applicants come from private companies, universities, and public-private partnerships. The United States, Europe, China, Canada, and the Republic of Korea lead the patent race in this area. The most-recorded IPC code is A61P33/06, related to the chemical substances or pharmaceutical formulations showing antimalarials activity. Most of the time, antimalarial drugs were made from quinine, artemisinin, trioxolane, naphthoquinones, and isoquinoline derivatives. Quinine and artemisinin are well-established classes of antimalarials with the maximum number of antimalarial drugs in the market. The research and innovations disclosed in most patents were focused on exploring or evaluating the new scaffolds and their mechanism of action against the normal and resistant malarial parasite. In conclusion, it has been found that various scaffolds are needed to be explored further in search of new antimalarial compounds.